Long-Term Cultured Human Term Placenta-Derived Mesenchymal Stem Cells of Maternal Origin Displays Plasticity - Vikram Sabapathy; Saranya Ravi; Vivi Srivastava; Alok Srivastava; Sanjay Kumar (Stem Cells International)
Mesenchymal stem cells (MSCs) are an alluring therapeutic resource because of their plasticity, immunoregulatory capacity and ease of availability. Human BM-derived MSCs have limited proliferative capability, consequently, it is challenging to use in tissue engineering and regenerative medicine applications. Hence, placental MSCs of maternal origin, which is one of richest sources of MSCs were chosen to establish long-term culture from the cotyledons of full-term human placenta. Flow analysis established bonafied MSCs phenotypic characteristics, staining positively for CD29, CD73, CD90, CD105 and negatively for CD14, CD34, CD45 markers. Pluripotency of the cultured MSCs was assessed by in vitro differentiation towards not only intralineage cells like adipocytes, osteocytes, chondrocytes, and myotubules cells but also translineage differentiated towards pancreatic progenitor cells, neural cells, and retinal cells displaying plasticity. These cells did not significantly alter cell cycle or apoptosis pattern while maintaining the normal karyotype; they also have limited expression of MHC-II antigens and are Naive for stimulatory factors CD80 and CD 86. Further soft agar assays revealed that placental MSCs do not have the ability to form invasive colonies. Taking together all these characteristics into consideration, it indicates that placental MSCs could serve as good candidates for development and progress of stem-cell based therapeutics.